The World Book Dictionary (Vol.2) L-Z - Edited by Barnhart , Clarence L. and Barnhart, Robert K. (Chicago World Book Inc., 1998)
An English language dictionary which provides definitions, spellings, and pronunciations to more than 225,000 terms
Include Illustration
Keywords: English language